KAJIAN PROPORSI SARI NANAS DAN KONSENTRASI STARTER TERHADAP SIFAT KIMIA DAN ORGANOLEPTIK KEFIR NANAS - Haliem, Inka Antonia Permata; Nugerahani, Ira; Rahayu, Endang Sri (Jurnal Teknologi Pangan dan Gizi, 2017)
Pineapple especially Queen variety is tropical fruit that is widely cultivated in various regions in Indonesia. Kefir grain is a culture that contains Lactic Acid Bacteria (LAB), Acetic Acid Bacteria and yeast. This study aims to determine the proportion of pineapple juice and concentration of starter on chemical and sensory properties of pineapple kefir. The experiental design used Randomized Block Design with factorial design that is proportion of pineapple juice that include pineapple juice N0 (without adding water), N1 (1:1) and N2 (1:2) and so the concentration of starter (1% (v/v) and 10% (v/v)). Each treatment repeated 4 times. Chemical parameters tested include total dissolved solids, vitamin C and alcohol content, while sensory parameters include the level of preference for color, aroma, taste and sparkling impression. Analysis of total yeast and LAB in kefir is use as supporting data. The data obtained were statistically analyzed by ANOVA (Analysis of Varians) at Î± = 5% and if there was a significant difference, then it continued by DMRT (Duncan's Multiple Range Test) test to determine which level of treatment that give significant differences. Higher pineapple juice increase total dissolved solids, vitamin C and alcohol content and increase and preference for colour, aroma, taste and sparkling impression. Higher starter concentrations descrease total dissolved solids and increase between vitamin C and alcohol content, descrease preference of aroma, taste and sparkling impression. The best treatment was pineapple juice without adding water (N0) and starter 1% with total value 0,95.